Phonological and phonetic competence: between grammar, signal processing, and neural activity - Hubert Truckenbrodt (Frontiers Research Topics, 2016)
The present collection of articles brings together experimental work in the field of segmental and prosodic processing and representation in phonology and phonetics. Contributions focus on the exploration of human cognitive, articulatory, and perceptual abilities dealing with all types of phonetic and phonological entities. Main topics of investigation include: (1) sounds and sound-changing processes-systemic and functional aspects, (2) prosodic units such as syllables and metrical feet-systemic properties, processing, and phonetic consequences, and (3) tones as building blocks of the sentence melody-their relation to the level of linguistic expressions on the one hand, their phonetic realization (e.g., tonal height and contours) and perception on the other hand. In addition, topics (1) and (2) extend to the question how phonological representations are stored in the mental lexicon: specified minimally in terms of categorical phonological information or as variable phonetic imprint of the exemplars in the input. Diagonally to these thematic domains, the present Research Topic shows a strong focus on up-to-date experimental approaches, going far beyond traditional linguistic analysis, and making use of psycho- and neurolinguistic methodologies.